Annual Plan of 1994-95 Himachal Pradesh - Planning Commission (Planning Commission, 1994)
The estimates of State Domestic Product (State Income) is the most commonly used economic indicator for measuring the general economic health of the State. The study of inter-sectoral distribution of State Domestic Product shows the cumulative effect of development efforts made in various sectors of the economy. After the release of the new series of National Accounts Statistics by Central Statistical Organisation in February, 1989 which is based on 1980-81 price's, this State also brought-out a new series of estimates; on similar lines.
Planning Department, Government Himachal Pradesh